Acute lymphoblastic leukemia and toxoplasmosis - Hiçsönmez, Gönül; Kanra, Güler; Gürsel, Türkiz; Yetkin, Sevgi; Altıntaş, Kürşat (The Turkish Journal of Pediatrics, 1979)
A 15-year-old girl with ALL developed toxoplasmosis while she was in remission. Most of the acquired toxoplasma infections in compromised hosts are diagnosed at autopsy. The importance of antemortem diagnosis and the good response to the treatment in our patient are discussed.